Do Individual Traits Associate with Ethical Judgment? - Mansori, Shaheen; Rezaee, Zabihollah; Homayoun, Saeid; Noghondari, Ali Taebi (Canadian Center of Science and Education, 2015)
Existence and persistence of financial scandals and crises has invigorated more interest in ethical judgment and behavior of policymakers, regulators, and executives throughout the world. These events have weak ened the trust among the public and investors’ confidence towards the financial markets globally and their financial reports. In this paper, we examined the role of individual traits in ethical judgment process and develop a model of assessing the effectiveness of the identified individual traits. We conducted a survey among 280 undergraduate business students at five private and public universities in Malaysia. We identified that gender identification, religiosity, ethnicity, and basic individual values are important considerations in making ethical judgment. These results suggested that personal traits and psychological factors play an important role in the ethical judgment process